THE MEANING CONSTRUCTION OF EXOCENTRIC NOUN-NOUN COMPOUNDS IN THAI - Weerayuth, Worraluck; วงษ์ไทย นันทนา (Thai Interdisciplinary and Sustainability Review, 2023)
This article aims to analyze the meaning construction and the meaning process of exocentric noun-noun compounds in Thai based on Conceptual Metaphor Theory and Conceptual Metonymy Theory. The data were collected from 1,919 noun-noun compounds appearing in Royal Institute Dictionary and Klangkam (revised edition). The research has found that there are 406 noun-noun compounds which are exocentric compound. There are 4 types of the meaning construction of exocentric noun-noun compounds in Thai including 1) exocentric compound with metaphorical head and metaphorical modifier 2) exocentric compound with metaphorical head and metonymical modifier 3) exocentric compound with metonymical head and metonymical modifier and 4) exocentric compound with metonymical head and metaphorical modifier. The meaning of exocentric compounds in Thai is figurative meaning. The meaning process of exocentric compounds in Thai involving metaphor and metonymy. The study shows that the cognitive process of Thai native speakers is metaphorical and metonymical.